Создание научного задела для формирования новых информационных ресурсов (на примере проблемно ориентированных баз данных геологической тематики) (Библиосфера)
The article presents materials of initial stages of new bibliographic data bases generating in SPSTL SB RAS on geology «Methane in coal mines» and «Studying the Quaternary period in Siberia and the Far East».